Dosis de ácido indolbutirico en dos tipos de sustrato para la propagación vegetativa de estaquillas de canela (cinnamomun sp.) en cámaras de sub irrigación en la región San Martín - Perú - Rueda Sandoval, Luis Enrique (2013)
The present thesis entitled "Dose indolebutyric acid in two types of substrate for vegetative propagation of cuttings of Canela (Cinnamomum sp.) In irrigation sub cameras in the San Martin - Peru", aimed to determine the effect two types of substrates for rooting of Canela (Cinnamomum sp) in sub chamber irrigation and determine the effect of four doses of indole butyric acid (IBA) on the rooting of cuttings of Canela (Cinnamomum sp). The research was performed at the Research Institute of the Peruvian Amazon (IIAP) San Martín Morales district, province and department of San Martin, whose UTM coordinates are: N 9283654 and E 0347742 at an altitude of 332 m The variables evaluated were: percentage of rooting, number of roots, root length increased, percentage of germination, callus percentage, percentage of defoliation and percentage of rot. Cuttings were used Canela (Cinnamomum sp.) Cinnamon from plants located at Km 26 road Yurimaguas - Tarapoto. The factors and levels studied were: A: substrate type (a1 = medium sand, coarse sand = a2), B: dose hormone (b1 = 0%, b2 = 0.2%; b3 = 0.4%; b4 = 0.6%; b5 = 0.8%) for which we used a completely randomized design with double factorial arrangement (2x5) with two levels for Factor A (type of substrate) and 5 levels for factor B (indolebutyric acid dose) and with 3 replicates. The most relevant conclusions were: developed in sand treatments showed the higher average in rooting (38.33%), number of roots from cuttings (1.65), primary root length (2.34 cm) and lower mortality averages (40.2%) and callus (31.33%). AIB application doses below 0.4% and about 0.6% affected the development of the roots. Applications treatments 0.6% (B3) and 0.4% (B2) had the highest AIB averages rooting percentage (45.83% and 33.33%), number of roots from cuttings (1.78 and 1.83 roots), root length main (2.02 cm and 1.93 cm) and 52.08% - 47.92% of callus in canela cuttings and lower average mortality of cuttings with 19.25% and 28.25% respectively.